1991
DOI: 10.1177/0148607191015006612
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Ratio of Individual Branched‐Chain Amino Acids in Total Parenteral Nutrition of Injured Rats

Abstract: In this study, we investigated the optimal ratio of individual branched-chain amino acids (BCAA) in a balanced amino acid infusion in laparotomized rats. The total BCAA contents of four amino acid infusions were fixed at 31% of total amino acids. The weight ratios of individual BCAA (isoleucine:leucine:valine) in the solutions were 1:0.5:1, 1:1:1, 1:2:1, and 1:4:1, respectively. The laparotomized rats were infused with about 140 mg (experiment 1) and 100 mg (experiment 2) of nitrogen and 10 g of glucose daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In addition, it is required to meet sensorial and functional quality and to have an acceptable cost for offering an enteral formula to drink daily at home. Our BCAA-modified protein, designed to contain, as recommended, a BCAA:AAA ratio of 3 [34] and a Val:Ile:Leu ratio near to 1:1:2 [35], was able to improve the plasma amino acid imbalance. Additionally, its chemical score (100) could maintain for longer time the good protein nutrition without increasing plasma Met levels, as was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is required to meet sensorial and functional quality and to have an acceptable cost for offering an enteral formula to drink daily at home. Our BCAA-modified protein, designed to contain, as recommended, a BCAA:AAA ratio of 3 [34] and a Val:Ile:Leu ratio near to 1:1:2 [35], was able to improve the plasma amino acid imbalance. Additionally, its chemical score (100) could maintain for longer time the good protein nutrition without increasing plasma Met levels, as was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also in line with another study where four different BCAA ratios (leucine:isoleucine:valine), including 0.5:1:1, 1:1:1, 1.5:1:1; 2:1:1 and 4:1:1, were tested. The results revealed that the optimal BCAA ratio should vary between 1:1:1 and 2:1:1 [41]. A higher proportion of BCAAs was demonstrated to be suitable for hepatic failure and hepatic encephalopathy patients.…”
Section: Product Characteristicsmentioning
confidence: 96%
“… 111 Iwasawa et al investigated four ratios in an amino‐acid infusion fixed at 31% of total amino acids in laparotomized rats. 112 The weight ratios of individual BCAA (isoleucine : leucine : valine) in the solutions were 1 : 0.5 : 1, 1 : 1 : 1, 1 : 2 : 1, and 1 : 4 : 1. There was no marked difference in either nitrogen balance or urinary 3‐methyl‐histidine concentrations.…”
Section: Metabolismmentioning
confidence: 96%